The Concept of Logistics Development Strategy in Slovenia - Trupac, Igor; Jakomin, Igor (Promet - Traffic&Transportation, 2012)
What we can witness nowadays are the important changesand transformations of and in societies. Development strategiesof the countries demand taking into account the diversity ofindividual countries, i.e. the geographical, cultural, political,social and economic diversities. Each count1y should be consideredfrom this point of view.The effects of logistics as an overwhelming and pervadingactivity are felt in all areas of the socio-economic life. Space, inhabitedareas and logistics form a system, a whole that has to beconsidered as an integrated unit.The concept of the logistic development strategy in Sloveniashould take into account the interests of the government, of sectorsand companies, research and development policy, logisticalpolicy, the choice of the logistical activity, the choice of instrumentsfor the (macro )logistical policy, financing as well asinstitutional organising factors.